Power Converters for Medium Voltage Networks - Islam, Md. Rabiul; Guo, Youguang; Zhu, Jianguo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book examines a number of topics, mainly in connection with advances in semiconductor devices and magnetic materials and developments in medium and large-scale renewable power plant technologies, grid integration techniques and new converter topologies, including advanced digital control systems for medium-voltage networks. The book’s individual chapters provide an extensive compilation of fundamental theories and in-depth information on current research and development trends, while also exploring new approaches to overcoming some critical limitations of conventional grid integration technologies. Its main objective is to present the design and implementation processes for medium-voltage converters, allowing the direct grid integration of renewable power plants without the need for step-up transformers.
Introduction -- Power Converters for Small to Large-Scale Photovoltaic Power Plants -- Power Converter Topologies for Grid Integrated Medium-Voltage Applications -- Design and Characterization of High-Frequency Magnetic-Links Used in Power Electronic Converters -- FPGA-Based Digital Switching Controller for Multilevel Converters -- Experimental Validation of 1-kV Modular Multilevel Cascaded Converter with High-Frequency Magnetic-Link -- Design and Analysis of 11 kV and 33 kV Modular Multilevel Cascaded Converters -- Conclusions and Future Works.
Keywords: Renewable energy resources; Power electronics; Electronic circuits; Energy systems; Renewable and Green Energy; Power Electronics, Electrical Machines and Networks; Circuits and Systems; Energy Systems